2001
DOI: 10.1063/1.1407866
|View full text |Cite
|
Sign up to set email alerts
|

Heat Capacity of Liquids: Critical Review and Recommended Values. Supplement I

Abstract: A study was carried out in which new experimental data on heat capacities of pure liquid organic and some inorganic compounds were compiled, critically evaluated, and recommended values provided. Compounds included in the compilation have a melting point below 573 K. The bulk of the compiled data covers data published in the primary literature between 1993 and 1999 and some data of 2000. However, some data from older sources were also included. The data were taken from almost 1030 literature references. Parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
101
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(107 citation statements)
references
References 554 publications
5
101
0
1
Order By: Relevance
“…1-Propanol was measured between 10 K and 350 K, 1-pentanol between 85 K and 370 K. The heat capacities of the liquid phase of all compounds measured, in total 944 data points, are used to derive a correlation function with the variables T/K and n (number of carbon atoms in the chain). A survey and a critical evaluation and correlation of the heat capacities of the individual 1-alcohols is given in the monograph by Zá branský et al 4 The complete condensed phases of 1-propanol are reviewed by Wilthoit et al 5 We compare our results to the adiabatic calorimetry measurements reported by Parks et al 6 and Counsell et al 7 …”
Section: Introductionmentioning
confidence: 74%
“…1-Propanol was measured between 10 K and 350 K, 1-pentanol between 85 K and 370 K. The heat capacities of the liquid phase of all compounds measured, in total 944 data points, are used to derive a correlation function with the variables T/K and n (number of carbon atoms in the chain). A survey and a critical evaluation and correlation of the heat capacities of the individual 1-alcohols is given in the monograph by Zá branský et al 4 The complete condensed phases of 1-propanol are reviewed by Wilthoit et al 5 We compare our results to the adiabatic calorimetry measurements reported by Parks et al 6 and Counsell et al 7 …”
Section: Introductionmentioning
confidence: 74%
“…Accurate heat capacity data have a wide field of application in thermochemistry for calculating changes in reaction enthalpies and in chemical engineering for establishing energy balances. [1][2][3] The possible use of ionic liquids (ILs) as heat transfer for heat exchange in chemical plants and solar thermal power generation was discussed, and it was found that the imidazolium based ionic liquids present higher heat capacities per unit of volume that two high performance commercial thermal fluids. [4][5][6] The knowledge of the heat capacity is required for the evaluation of the applicability of the ionic liquids as heat transfer fluids.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters are related quantitatively by Q = C × m × (Δ T) (15) where c is a constant of proportionality representing specific heat capacity and m is the mass of oil samples. Specific heat capacities provide a convenient way of determining the heat added to, or removed from a material [11,12,22,24]. This work adopted the calorimetory method and the principle of conservation of energy stated as c 1 …”
Section: Specific Heat Capacitymentioning
confidence: 99%